2001
DOI: 10.2754/avb200170020133
|View full text |Cite
|
Sign up to set email alerts
|

A Field Study of Oxygen Consumption and Estimated Energy Expenditure in the Exercising Horse

Abstract: The major goal of this study was to estimate the aerobic and anaerobic contribution to energy expenditure in the running warmblood horse under field conditions. The oxygen consumption (VO 2 ) in 12 saddle horses was determined at rest, walk, trot, and canter and in 6 horses at gallop. In the 10 min immediately following exercise the relative oxygen debt (RD-VO 2 ) was measured. The horses were exercised by riders in the various gaits at speeds representing 15, 30, 50 and 70% of the their individual maximum spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 14 publications
2
8
0
Order By: Relevance
“…Therefore, the calculation of EE from VO 2 measurements provided an estimation of the total energy expended during exercise. EE values measured at the different gaits, ranging from 133 to 1095 J/min per kg BW from walk to canter, respectively, (R s = 0.98; P ⩽ 0.001) (Table 1), were concordant with previous data reported in horses exercised in field conditions (Meixner et al, 1981;Pagan et al, 1986;Hanak et al, 2001). The relationship between EE and HR was best described as a polynomial function for each horse, with coefficients of determination above 80% for Figure 1 Illustration of one horse equipped with the equine K4b 2 and Equimask during exercise on track.…”
Section: Field Cardio-respiratory Measurements In Arabian Endurance Hsupporting
confidence: 89%
“…Therefore, the calculation of EE from VO 2 measurements provided an estimation of the total energy expended during exercise. EE values measured at the different gaits, ranging from 133 to 1095 J/min per kg BW from walk to canter, respectively, (R s = 0.98; P ⩽ 0.001) (Table 1), were concordant with previous data reported in horses exercised in field conditions (Meixner et al, 1981;Pagan et al, 1986;Hanak et al, 2001). The relationship between EE and HR was best described as a polynomial function for each horse, with coefficients of determination above 80% for Figure 1 Illustration of one horse equipped with the equine K4b 2 and Equimask during exercise on track.…”
Section: Field Cardio-respiratory Measurements In Arabian Endurance Hsupporting
confidence: 89%
“…HR and VO 2 values recorded at each step were consistent with previous data obtained from field exercise tests in Saddle horses (Hanak et al, 2001;Votion et al, 2006) and endurance horses (Cottin et al, 2010) using portable devices (Table 1). The VCO 2 values observed in our study were not markedly underestimated, contrary to those reported by Votion et al (2006) and van Erck et al (2007).…”
supporting
confidence: 64%
“…47 Aliquots of expired gas were collected via tubes in the face mask, and the rider manipulated the bags that were used to collect the gas at each step of the exercise test. 47 Aliquots of expired gas were collected via tubes in the face mask, and the rider manipulated the bags that were used to collect the gas at each step of the exercise test.…”
Section: Measurement Of Oxygen Uptake In Fi Eld Exercisementioning
confidence: 99%